The Impact of Student Attachment on University Reputation: An Analysis of Perceived Quality and Perceived Value - Efi Fitriani (International Journal of Marketing and Digital Creative, 2024)
Many studies have referred to campus reputation but have not used the mediating variable of student attachment. This study aims to examine the impact of perceived quality and value on students and analyze how perceived quality and value affect university reputation through student attachment. The statistical population comprised students at campus X. The sampling technique used was simple random sampling on 212 students from Campus X in Bandung, Indonesia. The results show that value perception is positively and significantly influenced by perceived quality. Perceived quality and perceived value have a positive and significant impact on student attachment, student attachment has a positive and significant impact on university reputation, perceived quality has a positive and significant impact on university reputation through student attachment, and perceived quality has a positive and significant impact on perceived value through perception of quality. In the literature on consumer behavior, there are several studies that examine perceived quality on perceived value, perceived quality on student attachment, perceived value on student attachment, and student attachment on university reputation. The primary contribution of this research is to examine perceived quality and value of university reputation through student attachment. This research adds value to the consumer behavior literature by providing new insights into the determinants of university reputation in a private university.